Mathematical model of the aguilarite (Ag4SeS) leaching process in the presence of other refractory silver phases - R. M. Luna-Sánchez; G. T. Lapidus (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
In the present study, a series of cyanidation experiments were performed on a bulk sulfide concentrate which contained silver in four distinct phases, to determine its extraction rate, varying the oxygen concentration. The results showed that three of the four phases were refractory, aguilarite (Ag,iSeS) being the only leachable phase, and that the effect of the oxidant concentration is minimal. Mathematical simulations were performed, adjusting only the Damkohler number to adequately fit the experimental data. This model, and the mechanism implied, was compared with that found for acanthite (Ag2S) in a previous study, and the differences between the two discussed.